Quasi-Asymptotically Almost Periodic Vector-Valued Generalized Functions - Kostić, Marko; Pilipović, Stevan; Velinov, Daniel (Sarajevo Journal of Mathematics, 2020)
In this paper are introduced the notions of a quasi-asymptotically almost periodic distributions and quasi-asymptotically almost periodic ultradistributions with values in a Banach space, as well as some other generalizations of these concepts. Furthermore, some applications of the introduced concepts in the analysis of systems of ordinary differential equations are provided.